Paranoid Schizophrenia, Combined with Cannabinoids Use: Epidemiological, Etiopathogenetic and Clinical Aspects (Literature Review) - Kydon’, P. V. (Psychiatry, Neurology and Medical Psychology, 2016)
In recent studies interest of domestic and foreign researchers growth to comorbid pathology − a combination of psychiatric illness with substance use. The aim of the review was to examine the impact of the cannabinoids use in schizophrenic process and determine which aspects of paranoid schizophrenia, combined with the use of cannabinoids investigated insufficiently, is not covered in full, based on an analysis of the literature. Analysis of the literature suggests that the problem of combination of paranoid schizophrenia and cannabinoids use (both dependence on these substances and without it) is far from being resolved.